Boundary-value problem in an infinite layer
We establish necessary and sufficient conditions for a nonlocal two-point boundary-value problem in an infinite layer for the equation ^2 u(x,t) t^2 + P( x )u(x + h_1 ,t) t + Q( x )u(x + h_2 ,t) = 0, whereP(s) andQ(s) are polynomials ins∈ℂ m with constant coefficients, to have infinite type and be degenerate., number=3, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Antypko, I. I. and Semenova, N. O., year=1995, month=Mar., pages=400–402